The Etymology of the Gymnophiona of the World - Lavilla, Esteban O. (Herpetologia Brasileira, 2026)
The etymologies of the generic names and specific epithets of all the Gymnophiona described between 1758 and 2023 are presented, pinpointing their current taxonomic standing. Each reference includes illuminating excerpts from the original descriptions, or from the directly transcribed original etymology, to shed light on the nomenclatural origins.